2(4x-2)=3(2x-1)

Simple and best practice solution for 2(4x-2)=3(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x-2)=3(2x-1) equation:


Simplifying
2(4x + -2) = 3(2x + -1)

Reorder the terms:
2(-2 + 4x) = 3(2x + -1)
(-2 * 2 + 4x * 2) = 3(2x + -1)
(-4 + 8x) = 3(2x + -1)

Reorder the terms:
-4 + 8x = 3(-1 + 2x)
-4 + 8x = (-1 * 3 + 2x * 3)
-4 + 8x = (-3 + 6x)

Solving
-4 + 8x = -3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-4 + 8x + -6x = -3 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-4 + 2x = -3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + 2x = -3 + 0
-4 + 2x = -3

Add '4' to each side of the equation.
-4 + 4 + 2x = -3 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = -3 + 4
2x = -3 + 4

Combine like terms: -3 + 4 = 1
2x = 1

Divide each side by '2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 17x=3(3x+40) | | 2.4*16= | | c^2-5c+2=0 | | -6x+12=-30 | | 4+2(5+(-3))= | | 5x^2=-2-11x | | 72x^3-80x^4= | | 3.25+0.25(v)=14 | | 3y-3+4x-2=3x+3y-1 | | 7p=-5m | | v-4v+10=14 | | b/3-7=_33 | | -5(-2n-4)+5n=-100 | | 4x^2+12=3x | | 36m^3-8= | | 4n+19+3n+28=180 | | 2(−14−2y)/4 | | 3y-1+2y-1-4y=2y+3+y+1 | | -22x+22=x+7 | | -10x+9y=54 | | 6y+26=-7y | | x^2-y-9=0 | | 7.50/123.75 | | 6y+26=-7 | | 26x-13=0 | | D=3c+2 | | x-4-2x=5+3(2x-4) | | 3d^2-7d=0 | | 29+4x=9x | | 12x+5x-6=28 | | uuu=2 | | 5x-3/2 |

Equations solver categories